Epigenome-wide association study of rheumatoid arthritis identifies differentially methylated loci in B cells. (5th May 2017) - Julià, Antonio; Absher, Devin; López-Lasanta, María; Palau, Nuria; Pluma, Andrea; Waite Jones, Lindsay; Glossop, John R.; Farrell, William E.; Myers, Richard M.; Marsal, Sara
Abstract: Epigenetic regulation of immune cell types could be critical for the development and maintenance of autoimmune diseases like rheumatoid arthritis (RA). B cells are highly relevant in RA, since patients express autoantibodies and depleting this cell type is a successful therapeutic approach. Epigenetic variation, such as DNA methylation, may mediate the pathogenic activity of B cells. In this study, we performed an epigenome-wide association study (EWAS) for RA with three different replication cohorts, to identify disease-specific alterations in DNA methylation in B cells. CpG methylation in isolated B lymphocytes was assayed on the Illumina HumanMethylation450 BeadChip in a discovery cohort of RA patients ( N  =   50) and controls ( N  =   75). Differential methylation was observed in 64 CpG sites ( q  <   0.05). Six biological pathways were also differentially methylated in RA B cells. Analysis in an independent cohort of patients ( N  =   15) and controls ( N  =   15) validated the association of 10 CpG sites located on 8 genes CD1C, TNFSF10, PARVG, NID1, DHRS12, ITPK1, ACSF3 and TNFRSF13C, and 2 intergenic regions. Differential methylation at the CBL signaling pathway was replicated. Using an additional case-control cohort ( N  =   24), the association between RA risk and CpGs cg18972751 at CD1C ( P  =   2.26 × 10 −9 ) and cg03055671 at TNFSF10 ( P  =   1.67 × 10 −8 ) genes was further validated. Differential methylation at genes CD1C, TNFSF10, PARVG, NID1, DHRS12, ITPK1, ACSF3, TNFRSF13C and intergenic region chr10p12.31 was replicated in a cohort of systemic lupus erythematosus (SLE) patients ( N  =   47) and controls ( N  =   56). Our results highlight genes that may drive the pathogenic activity of B cells in RA and suggest shared methylation patterns with SLE.